The rise tone in short story narration: A case study of Malay ESL learners - Ahmad Nadzri, Fazyudi; Abdul Wahid, Mohd Ridwan; Pilus, Zahariah (2020)
Despite its importance in communication, ESL learners often face difficulties in using intonation appropriately due to cross-linguistic suprasegmental differences. Moreover, intonation is difficult for them to learn because its functions can change according to context (Mok, Yin, Setter & Mat Nayan, 2016). Given these challenges, the objective of this study was to investigate the application of one type of intonation – the rise tone – in the speech of such speakers. Sixty Malay ESL learners, comprising 30 males and 30 females, were asked to narrate a short story individually based on a series of pictures presented to them. Their speech samples were analysed auditorily and acoustically using Praat and their tone functions were identified using Brazil’s (1985, 1997) Discourse Intonation model. It was found that the learners applied the tone when they attempted to: (i) convey new and shared information, (ii) continue speaking, and (iii) present items in a list. In addition, there was a significant gender-based difference in the speakers’ application of the tone to convey new and shared information and to continue speaking. Findings may contribute details to Malaysian English phonology and shed more light on tone usage among ESL speakers.